Transporter mobile application: empowering your journey with reliable transport services - Zakaria, Noor Azura; Tajul Anuar, Ahmad Faiz (2024)
Transporter is a popular service within the IIUM community. It is an e-hailing service operated by the community itself. It is hosted on the Telegram app, which is available on Android, iOS, and desktop computers. However, there are various downsides related to handling user registration, transportation requests, and efficiency. To address these shortcomings, a transporter application was created as a mobile app. This project intends to create a mobile application employing the agile method and FlutterFlow, a low-code platform built on top of Flutter, an open-source development framework. At the same time, it improves on the current IIUM transporter system while retaining the features that make it so popular among the community.